INFLUENCE OF GRAPE SEED FLOUR ON THE QUALITY OF SAUSAGE BREAD - N. L. Naumova; A. A. Lukin; A. A. Sergeyev (Современная наука и инновации, 2022)
Grape seeds are one of the sources of natural antioxidants, and also contain a complex of essential and functional components involved in the full development of the human body. Grape seed extract is a valuable source of vitamins, minerals, fatty acids, tannins, etc.